A mixed-method exploratory assessment of provider-based stigma of opioid use disorder (OUD) and support for medications for opioid use disorder (MOUD) in carceral settings - Katherine J. McLean; Nathan E. Kruis; Eric Weintraub; Heather Fitzsimons; Christopher Welsh; Natalie Spicyn; Brook Kearley; William Altekruse; Nicholas Rowland; Annabelle Belcher (Harm Reduction Journal)
Abstract Background In 2019, the state of Maryland passed legislation requiring local detention centers to offer medications for opioid use disorder (MOUD) to all incarcerated individuals who met criteria for opioid use disorder (OUD). Four years later, many facilities remain out of compliance. Beyond issues of staffing, funding, and technical support, stigma may represent a barrier to MOUD implementation. Methods Using surveys and interviews among correctional professionals working in Maryland, the current exploratory study sought to identify barriers to MOUD implementation, including measures of provider-based stigma of OUD and support for MOUD. Results Quantitative and qualitative results revealed moderately high levels of OUD-related stigma and negative attitudes toward MOUD, with multivariable modeling revealing a statistically significant relationship between provider-based stigma of OUD and support for MOUD in correctional settings. Conclusion These findings suggest that stigma may be a significant barrier to MOUD implementation in local detention centers, even in the presence of legal mandates. Further, these results reveal the need for educational and anti-stigma campaigns targeted at correctional professionals who are charged with implementing policies that may contradict their previous learning or correctional training.